A Novel Heterocyclic System Based on Natural Epoxyalantolactone - Klochkov, Sergey G.; Pukhov, Sergey A.; Afanasieva, Svetlana V.; Neganova, Margarita E.; Ananiev, Ivan V.; Avila-Rodriguez, Marco; Tarasov, Vadim V.; Aliev, Gjumrakch (Frontiers in Chemistry, 2019)
Natural sesquiterpene lactones which contain an exocyclic methylene group in the β-position of the lactone ring react readily with N-nucleophiles. When studying the reaction of the natural epoxyalantolactone with the primary amines we demonstrate the formation of a new heterocyclic system - the hydrogenated benzo[g]furo[4,3,2-cd]indol-3(1H)-one. Spectral data on the characteristics of the synthesized compounds are presented. The data on the reaction mechanisms and its applicability for the preparation are discussed.